The Resistance of Laminated Bamboo Boards to Subterranean Termite (Coptotermes curvignathus Holmgren) - Ignasia M Sulastiningsih; Jasni Jasni (Masyarakat Peneliti Kayu Indonesia, 2012)
This study investigated the resistance of three-layer laminated bamboo boards (LBB’s) to subterranean termites (Coptotermes curvignathus Holmgren) according to the Indonesian standard (SNI 01.7207-2006). Bamboo strips for LBB fabrication were prepared from Gigantochloa pseudoarundinacea and assigned into 4 groups by pre-treatment methods namely: untreated, cold soaking in 5% boron solution for 2 hours, bleached by 17.5% and 20% hydrogen peroxide solutions. The LBB was formed by tannin resorcinol formaldehyde (TRF). Wheat flour was used as extender with two different concentrations (i.e., 2.5% and 5%) based on TRF weight. The results indicated that the resistances of LBB’s were much affected by pre-treatment methods. Applying different concentration of extender in TRF resin resulted in similar termite resistance of LBB’s against C. curvignathus Holmgren. Pre-treated of bamboo strips with 5% boron solution and bleached by 17.5% and 20% hydrogen peroxide solutions prior to be LBB manufactured improved the termite reistance of LBB’s against C. curvignathus Holmgren one level compared to untreated LBB. The termite-resistance of LBB made from untreated bamboo strips was categorized as class IV (poor) whereas those from boron- or hydrogen peroxide-treated bamboo strips belonged to class III (moderate).Key words: boron solution, hydrogen peroxide, laminated bamboo board, subterranean termite, tannin resorcinol formaldehyde